2023
DOI: 10.1590/1980-4415v37n77a15
|View full text |Cite
|
Sign up to set email alerts
|

Sucesiones matemáticas en el currículo de México en secundaria

Karina Nuñez-Gutierrez,
Guadalupe Cabañas-Sánchez

Abstract: Resumen En este artículo se identificaron y relacionaron los significados de las sucesiones matemáticas en los números naturales a través de su estructura conceptual, representaciones y modos de uso en el currículo mexicano de matemáticas de secundaria y en catorce libros de texto utilizados para la enseñanza y aprendizaje de las sucesiones en este nivel escolar. Para ello, se realizó un análisis didáctico enfocado en la dimensión de contenido matemático (RICO et al., 2008; RICO, 2012; RICO, MORENO, 2016). Los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Therefore, the data indicates that one of the representations that is most used in the textbooks of the three grades in secondary school is the pictorial one. In relation to research on numerical sequences or patterns in other countries, aspects were identified that coincide with those found in this research (Rivera and Becker 2005;Castro, 2013;Wilkie, 2016;Nuñez-Gutiérrez & Cabañas-Sánchez, 2023).…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…Therefore, the data indicates that one of the representations that is most used in the textbooks of the three grades in secondary school is the pictorial one. In relation to research on numerical sequences or patterns in other countries, aspects were identified that coincide with those found in this research (Rivera and Becker 2005;Castro, 2013;Wilkie, 2016;Nuñez-Gutiérrez & Cabañas-Sánchez, 2023).…”
Section: Resultssupporting
confidence: 75%
“…In Mexico, the 2011, 2017 and 2022 mathematics study plan and programs (SEP, 2011;SEP, 2017;SEP, 2022) establish that sequences are studied during the three years of secondary school, through numerical and figural patterns in order to promote skills of construction, formulation and obtain the general rule of the sequence (Nuñez-Gutiérrez & Cabañas-Sánchez, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations